The Technological Platform as a Communication Tool for the Implementation of the Financial Capacity of Russian Economy - ВладимироваОльга Николаевна; ДягельОксана Юрьевна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2012)
Authors: Olga Nikolaevna Vladimirova - National Research University "Higher School of Economics." Oksana Yurevna Dyagel - National Research University "Higher School of Economics." The article deals with the essence of the concept of "technology platforms", his relationship with the concept of "cluster"; separately considered their financing is a comparative analysis of approaches to the formation of Russian and European technological platforms, including in terms of attracting financial resources for their functioning; highlighted the problem of creating technological platforms.